How Can Academics Engage as Public Intellectuals on Social Media Platforms? A Foucauldian Discourse Analysis of Social Media Guidelines - Yoon, Ee-Seul; Moore, Shannon D. M. (Journal of Contemporary Issues in Education, 2024)
This paper examines how university policies are written to regulate the conduct of academics on social media, particularly the extent to which academics are discouraged from acting as public intellectuals on social media. Drawing on Michel Foucault, we analyze the social media guidelines developed by Canada’s 15 research-intensive universities, known as the U15. Our analysis illuminates that the guidelines articulate particular power relations between academics and their universities – relations that are increasingly influenced by the corporatization of higher education in the era of neoliberalism. We argue that social media guidelines represent emblematic discourses that discipline academics working in highly corporatized universities. Faculty may thus be less inclined to act as public intellectuals.